Jacques Derrida and the challenge of history - Gaston, Sean (Rowman & Littlefield International, 2019)
In the first book-length study of Derrida and the question of history, and in response to the 2016 publication of Derrida's 1964-1965 seminar on Heidegger and history, Sean Gaston explores Derrida's own political responses to the historical events of his time. He argues that contemporary philosophy can provide a basis for thinking about history.